Previous Article in Journal
Public Opinion Spread and Guidance Strategy under COVID-19: A SIS Model Analysis
Previous Article in Special Issue
New Inequalities and Generalizations for Symmetric Means Induced by Majorization Theory

Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

Context-Free Grammars for Several Triangular Arrays

by
Roberta Rui Zhou
1,*,
Jean Yeh
2,* and
Fuquan Ren
3
1
School of Mathematics and Statistics, Northeastern University at Qinhuangdao, Qinhuangdao 066004, China
2
Department of Mathematics, National Kaohsiung Normal University, Kaohsiung 000800, Taiwan
3
School of Science, Yanshan University, Qinhuangdao 066004, China
*
Authors to whom correspondence should be addressed.
Axioms 2022, 11(6), 297; https://doi.org/10.3390/axioms11060297
Submission received: 26 April 2022 / Revised: 9 June 2022 / Accepted: 10 June 2022 / Published: 20 June 2022

Abstract

:
In this paper, we present a unified grammatical interpretation of the numbers that satisfy a kind of four-term recurrence relation, including the Bell triangle, the coefficients of modified Hermite polynomials, and the Bessel polynomials. Additionally, as an application, a criterion for real zeros of row-generating polynomials is also presented.
MSC:
05A05; 05A15

1. Introduction

Let A denote an alphabet, the letters of which are considered as independent commutative indeterminates. Then, the context-free grammar G over A is defined as a set of replacement rules that substitute the letters in A with formal functions on A. The formal derivative D is a linear operator, which is defined relative to a context-free grammar G (see [1]). For example, for $A = { u , v }$ and $G = { u → u v , v → v }$, then $D ( u ) = u v , D 2 ( u ) = u ( v + v 2 ) , D n ( u ) = u ∑ k = 1 n S ( n , k ) v k$, where $S ( n , k )$ is the Stirling number of the second kind, i.e., the number of ways to partition $[ n ]$ into k blocks.
In [2], Hao, Wang, and Yang presented a grammatical interpretation of the numbers $T ( n , k )$ that satisfy the following three-term recurrence relation:
$T ( n , k ) = ( a 1 n + a 2 k + a 3 ) T ( n − 1 , k ) + ( b 1 n + b 2 k + b 3 ) T ( n − 1 , k − 1 ) .$
Very recently, there is a large literature devoted to the numbers $t ( n , k )$ that satisfy the following four-term recurrence relation (see [3,4,5,6,7]):
$t n , k = ( a 1 n + a 2 k + a 3 ) t n − 1 , k + ( b 1 n + b 2 k + b 3 ) t n − 1 , k − 1 + ( c 1 n + c 2 k + c 3 ) t n − 1 , k − 2 ,$
with $t 0 , 0 = 1$ and $t n , k = 0$, unless $0 ≤ k ≤ n$. For example, Ma [8] showed that if $G = { x → x y , y → y z , z → y 2 }$, then $D n ( x 2 ) = x 2 ∑ k = 0 n R ( n + 1 , k ) y k z n − k$, where $R ( n , k )$ is the number of permutations in $S n$ with k alternating runs, and it satisfies the recurrence relation
$R ( n , k ) = k R ( n − 1 , k ) + 2 R ( n − 1 , k − 1 ) + ( n − k ) R ( n − 1 , k − 2 )$
with the initial conditions $R ( 1 , 0 ) = 1$ and $R ( 1 , k ) = 0$ for $k ≥ 1$.
Let
$a ( n , k ) = ∑ i = 0 n S ( n , i ) i k$
for $0 ≤ k ≤ n$. Clearly, $a ( n , k )$ is the number of set partitions of ${ 1 , 2 , … , n }$ in which exactly k of the blocks have been distinguished. The numbers $a ( n , k )$ satisfy the recurrence relation
$a ( n + 1 , k ) = a ( n , k − 1 ) + ( k + 1 ) a ( n , k ) + ( k + 1 ) a ( n , k + 1 ) ,$
with $a ( 0 , 0 ) = 1$, $a ( 0 , k ) = 0$ for $k ≠ 0$ (see [9,10]). The triangular array ${ a ( n , k ) } n , k$ is known as the classical Bell triangle and is given as follows:
$1 1 1 2 3 1 5 10 6 1 15 37 31 10 1 ⋮ ⋱ .$
It appears that $a ( n , 0 ) = ∑ i = 0 n S ( n , i ) = B n$, which implies that the first column of the triangle array is made up of the Bell numbers $B n$. A natural question is whether there exists a grammatical interpretation of the numbers $a ( n , k )$.
This paper is motivated by exploring the grammatical interpretation of the triangular array ${ B ( n , k ) } 0 ≤ k ≤ n$ that satisfies the following four-term recurrence relation
$B ( n + 1 , k ) = ( a 1 n + a 2 k + a 3 ) B ( n , k − 1 ) + ( b 1 n + b 2 k + b 3 ) B ( n , k ) + ( k + 1 ) c B ( n , k + 1 ) ,$
where $a i , b i$, and c are integers for $1 ≤ i ≤ 3$ with $B ( 0 , 0 ) = 1$ and $B ( 0 , k ) = 0$ if $k ≠ 0$. In Section 2, we present grammatical interpretations of the triangular array ${ B ( n , k ) }$. In Section 3, we present grammatical interpretations of several combinatorial sequences, including the Bell triangle, the modified Hermite polynomials, the Bessel polynomials, and so on. In Section 4, we show the result of the real-rootedness of row-generating functions for ${ B ( n , k ) }$, and apply the proposed criteria to the Bell triangular array as an example.

2. Grammatical Interpretations of the Triangular Array $B ( n , k )$

We now present the first main result of this paper.
Theorem 1.
Suppose that $a i$, $b i$, and c are integers for $1 ≤ i ≤ 3$. Let
$G = { I → ( a 2 + a 3 ) I X + b 3 I Y ; X → ( a 1 + a 2 ) X 2 + ( b 1 + b 2 ) X Y + c Y 2 ; Y → a 1 X Y + b 1 Y 2 } .$
Then, we have
$D n ( I ) = I ∑ k ≥ 0 B ( n , k ) X k Y n − k ,$
where the coefficients $B ( n , k )$ satisfy the recurrence relation (3).
Proof.
Note that $D ( I ) = ( a 2 + a 3 ) I X + b 3 I Y$. Suppose that (4) holds for n. Then, by induction, we obtain
$D n + 1 ( I ) = D { D n ( I ) } = ∑ k ≥ 0 B ( n , k ) D ( I ) X k Y n − k + ∑ k ≥ 0 B ( n , k ) I D ( X k ) Y n − k + ∑ k ≥ 0 B ( n , k ) I X k D ( Y n − k ) .$
Applying the rules of G, we can derive
$∑ k ≥ 0 B ( n , k ) I ( a 2 + a 3 ) X k + 1 Y n − k + ∑ k ≥ 0 B ( n , k ) I b 3 X k Y n + 1 − k + ∑ k ≥ 0 B ( n , k ) k I X k − 1 Y n − k { ( a 1 + a 2 ) X 2 + ( b 1 + b 2 ) X Y + c Y 2 } + ∑ k ≥ 0 B ( n , k ) ( n − k ) I X k Y n − k { a 1 X + b 1 Y } .$
Collate and merge similar items
$∑ k ≥ 0 B ( n , k ) ( a 2 + a 3 + k ( a 1 + a 2 ) + ( n − k ) a 1 ) I X k + 1 Y n − k + ∑ k ≥ 0 B ( n , k ) ( ( n − k ) b 1 + k ( b 1 + b 2 ) + b 3 ) I X k Y n + 1 − k + ∑ k ≥ 0 B ( n , k ) k c I X k − 1 Y n − k + 2 .$
Extracting the coefficient of $I X k Y n + 1 − k$, we obtain (3). This completes the proof. □
Along the same lines of the proof of Theorem 1, one can easily derive the following result.
Proposition 1.
Let
$G = { I → ( a 2 + a 3 ) I X + b 3 I Y ; X → ( a 1 + a 2 ) X 2 + ( b 1 + b 2 ) X Y + c Y 2 ; Y → d X 2 + a 1 X Y + b 1 Y 2 } .$
Then, we have
$D n ( I ) = I ∑ k ≥ 0 M ( n , k ) X k Y n − k ,$
where $M ( n , k )$ satisfy the following five-term recursive relation:
$M ( n + 1 , k ) = ( n − k + 2 ) d M ( n , k − 2 ) + ( a 1 n + a 2 k + a 3 ) M ( n , k − 1 ) + ( b 1 n + b 2 k + b 3 ) M ( n , k ) + ( k + 1 ) c M ( n , k + 1 ) .$
where $a i$, $b i$, c, and d are integers for $1 ≤ i ≤ 3$.
When $d = 0$, the recurrence relation (5) is degenerated into (3).

3. Applications

3.1. The Bell Triangle

The Bell triangle was proposed by Aigner [9] to provide a characterization of the sequence of Bell numbers by means of the determinants of Hankel matrices. As a special case of Theorem 1, we now present a grammatical interpretations of the Bell triangle.
Proposition 2.
Let $G = { I → I X + I Y ; X → X Y + Y 2 ; Y → 0 }$. Then, we have
$D n ( I ) = I ∑ k ≥ 0 a ( n , k ) X k Y n − k = I Y n a n ( X Y ) .$
Note $D n ( X ) = X Y n + Y n + 1$, $D n ( Y ) = 0$. From Leibniz’s formula, we obtain the following corollary:
Corollary 1.
For $n ≥ 0$, we have
$a n + 1 ( x ) = ∑ i = 0 n n k a k ( x ) ( x + 1 )$
Let $D n ( I X ) = I ∑ k = 0 n + 1 b ( n + 1 , k ) X k Y n + 1 − k$. It is routine to verify that
$b ( n + 2 , k ) = b ( n + 1 , k − 1 ) + ( k + 1 ) b ( n + 1 , k ) + ( k + 1 ) b ( n + 1 , k + 1 ) ,$
with $b ( 1 , 1 ) = 1$ and $b ( 1 , k ) = 0$ when $k ≠ 1$. Since $D n + 1 ( I ) = D n ( I X ) + D n ( I Y )$, it follows that $a ( n + 1 , k ) = b ( n + 1 , k ) + a ( n , k )$.
Note that $D n ( X ) = Y n ( X + Y )$. Then,
$b ( n + 1 , k ) = ∑ i = 0 n + 1 − k n i + k − 1 a ( i + k − 1 , k − 1 ) + ∑ i = 0 n − k n i + k a ( i + k , k ) .$

3.2. On the Coefficients of Modified Hermite Polynomials

The modified Hermite polynomials have the following form:
$h ( 0 , x ) = 1 h ( 1 , x ) = x h ( 2 , x ) = x 2 + 1 h ( 3 , x ) = x 3 + 3 x h ( 4 , x ) = x 4 + 6 x 2 + 3 h ( 5 , x ) = x 5 + 10 x 3 + 15 x h ( 6 , x ) = x 6 + 15 x 4 + 45 x 2 + 15$
If $n − k ≥ 0$ is even, let
$T ( n , k ) = n ! 2 n − k 2 ( n − k 2 ) ! k ! .$
Otherwise, set $T ( n , k ) = 0$. It should be noted that the numbers $T ( n , k )$ are the coefficients of the modified Hermite polynomials (see A099174 [11]) and
$T ( n + 1 , k ) = T ( n , k − 1 ) + ( k + 1 ) T ( n , k + 1 ) .$
Using Theorem 1, we obtain the following proposition.
Proposition 3.
Let $G = { I → I X ; X → Y 2 ; Y → 0 }$. Then, we have
$D n ( I ) = I ∑ k ≥ 0 T ( n , k ) X k Y n − k = I Y n h ( n , X Y ) .$
Note that $D n ( X ) = 0 ( n ≥ 2 )$. From Leibniz’s formula, we obtain the following corollaries:
Corollary 2.
For $n ≥ 0$, we have
$h ( n + 1 , x ) = x h ( n , x ) + n h ( n − 1 , x )$
Corollary 3.
For $n ≥ k ≥ 1$, we have
$T ( n + 1 , k ) = T ( n , k − 1 ) + n T ( n − 1 , k )$

3.3. The Bessel Polynomials

As a well-known orthogonal sequence of polynomials, the Bessel polynomials $y n ( x )$ were introduced by Krall and Frink in [12], which can be defined as the polynomial solutions of the second-order differential equation
$x 2 d 2 y n ( x ) d x 2 + 2 ( x + 1 ) d y n ( x ) d x = n ( n + 1 ) y n ( x )$
After that, the Bessel polynomials have been extensively studied and applied (see [13,14,15]). Moreover, the polynomials $y n ( x )$ can be generated by using the Rodrigues formula (see [11] [A001498]):
$y n ( x ) = 1 2 n e 2 / x d n d x n ( x 2 n e − 2 / x )$
Explicitly, we can obtain
$y n ( x ) = ∑ k = 0 n ( n + k ) ! ( n − k ) ! k ! x 2 k$
Let
$H ( n , k ) = ( n + k ) ! 2 k ( n − k ) ! k !$
Then,
$y n ( x ) = ∑ k = 0 n H ( n , k ) x k$
It is easy to verify that
$H ( n + 1 , k ) = H ( n , k ) + ( n + k ) H ( n , k − 1 )$
The polynomials $y n ( x )$ satisfy the recurrence relation
$y n + 1 ( x ) = ( 2 n + 1 ) x y n ( x ) + y n − 1 ( x ) , f o r n ⩾ 0$
with initial conditions $y − 1 ( x ) = y 0 ( x ) = 1$. The first three Bessel Polynomials are expressed as
$y 1 ( x ) = 1 + x , y 2 ( x ) = 1 + 3 x + 3 x 2 , y 3 ( x ) = 1 + 6 x + 15 x 2 + 15 x 3 .$
We present here a grammatical characterization of the Bessel polynomials $y n ( x )$.
Proposition 4.
Let $G = { I → I X + I Y ; X → 2 X 2 ; Y → X Y }$. Then, we have
$D n ( I ) = I ∑ k ≥ 0 H ( n , k ) X k Y n − k = I Y n y n ( X / Y ) .$
Note that $D n ( X ) = n ! 2 n X n + 1$ and $D n ( Y ) = ( 2 n − 1 ) ! ! X n Y$. From Leibniz’s formula, we obtain the following corollary:
Corollary 4.
For $n ≥ 0$, we have
$y n + 1 ( x ) = ∑ k = 0 n n k ( 2 n − 2 k − 1 ) ! ! y k ( x ) x n − k + ∑ k = 0 n n ! 2 n − k k ! y k ( x ) x n − k + 1 .$

3.4. The Exponential Riordan Array $[ exp ( x / ( 1 − x ) ) , x / ( 1 − x ) ]$

Definition 1
(see [16]). The exponential Riordan group G is a set of infinite lower-triangular integer matrices, and each matrix in G is defined by a pair of generating function $g ( x ) = g 0 + g 1 x + g 2 x 2 + ⋯$ and $f ( x ) = f 1 x + f 2 x 2 + ⋯$, with $g 0 ≠ 0$ and $f 1 ≠ 0$. The associated matrix is the matrix whose i-th column has exponential generating function $g ( x ) f ( x ) i / i !$ (columns marked from 0). The matrix corresponding to the pair $f , g$ is defined by $[ g , f ]$.
Let $R ( n , k )$ be the $( n , k )$-th element in the matrix $[ exp ( x / ( 1 − x ) ) , x / ( 1 − x ) ]$. The associated Riordan array is given as follows:
$1 1 1 3 4 1 13 21 9 1 73 136 78 16 1 ⋮ ⋱$
From A059110 [11], we see that
$R ( n , k ) = ∑ i = 0 n L ′ ( n , i ) i k$
for $0 ≤ k ≤ n$, where $L ′ ( n , i ) = n ! i ! n − 1 i − 1$ are unsigned Lah numbers. It is routine to verify that
$R ( n + 1 , k ) = R ( n , k − 1 ) + ( n + k + 1 ) R ( n , k ) + ( k + 1 ) R ( n , k + 1 ) .$
Hence, by Theorem 1, we obtain the following Proposition.
Proposition 5.
Let
$G = { I → I X + I Y ; X → 2 X Y + Y 2 ; Y → Y 2 }$
Then, we have
$D n ( I ) = I ∑ k ≥ 0 R ( n , k ) X k Y n − k : = I Y n r n ( X Y ) .$
Note $D n ( X ) = ( n + 1 ) ! x Y n + n n ! Y n + 1$, $D n ( Y ) = n ! Y n + 1$. From Leibniz’s formula, we obtain the following corollary:
Corollary 5.
For $n ≥ 0$, we have
$r n + 1 ( x ) = ∑ k = 1 n n k ( n − k + 1 ) ! r k ( x ) ( x + 1 )$
In Table 1, we list some combinatorial sequences that satisfy (3). More examples can be found in similar tables in [17,18,19]. By using Theorem 1, we give the grammatical interpretation of the corresponding sequences, so that we can obtain more convolution formulas.

4. Real Rootedness

In this section, as an application, we will pay attention to the property of real roots of the row-generating functions in the array ${ B ( n , k ) } 0 ≤ k ≤ n$ in (3). For the sake of proving our results, some known results should be introduced beforehand.
Let ${ P n ( x ) }$ denote a Sturm sequence, which is a sequence of standard polynomials meeting the condition of $deg P n = n$ and $P n − 1 ( r ) P n + 1 ( r ) < 0$ whenever $P n ( r ) = 0$ and $n ≥ 1$. Let RZ represent the set of polynomials with only real roots. ${ P n ( x ) }$ is known as a generalized Sturm sequence (GSS) if $P n ∈ R Z$ and zeros of $P n ( x )$ are separated by those of $P n − 1 ( x )$ for $n ≥ 1$. As a special case of Corollary $2.4$ in Liu and Wang [20] (also see Zhu, Yeh, and Lu [7]), the following result provides a unified method to many polynomials with only real zeros.
Lemma 1.
Let ${ P n ( x ) }$ be a sequence of polynomials with nonnegative coefficients and $0 ≤ deg P n − deg P n − 1 ≤ 1$. Suppose that
$P n ( x ) = ( a n x + b n ) P n − 1 ( x ) + x ( c n x + d n ) P n − 1 ′ ( x )$
where $a n$, $b n ∈ R$, and $c n ≤ 0$, $d n ≥ 0$. Then, ${ P n ( x ) } n ≥ 0$ is a generalized Sturm sequence.
For nonnegative array $B ( n , k )$, which satisfies the recurrence relation (3), it is sufficient to assume that, for $n ≥ 1$,
$a 1 n + a 2 k + a 3 − a 1 ≥ 0 for 1 ≤ k ≤ n , b 1 n + b 2 k + b 3 − b 1 ≥ 0 for 0 ≤ k ≤ n − 1 , c ( k + 1 ) ≥ 0 for 0 ≤ k ≤ n − 2 ,$
which is equivalent to
$a 1 ≥ 0 , a 1 + a 2 ≥ 0 , a 2 + a 3 ≥ 0 , b 1 ≥ 0 , b 1 + b 2 ≥ 0 , b 3 ≥ 0 , c ≥ 0 .$
Define $B n ( x ) = ∑ k ≥ 0 n B ( n , k ) x k$ ($n ≥ 0$) as the row-generating functions of $B ( n , k )$. Thus, $B 0 ( x ) = 1$ and
$B 1 ( x ) = b 3 + ( a 2 + a 3 ) x .$
Moreover, it turns out that $B n ( x )$ follows from the recurrence relation (3) as
$B n ( x ) = [ b 1 n + b 3 − b 1 + ( a 1 n + a 2 + a 3 − a 1 ) x ] B n − 1 ( x ) + ( c + b 2 x + a 2 x 2 ) B n − 1 ′ ( x ) ,$
which implies that
$deg ( B n ( x ) ) − deg ( B n − 1 ( x ) ) ≤ 1$
for each n.
Theorem 2.
Let ${ B ( n , k ) } n , k ≥ 0$ be the array defined in (3). Assume that $b 2 = a 2 + c$. Then, we have the following results:
(i)
There exist polynomials $A n ( x )$ for $n ≥ 0$ such that
$B n ( x ) = a n ( 1 + x ) n A n ( d 1 + x ) ,$
where $A n ( x )$ satisfies the recurrence relation
$A n ( x ) = 1 a { ( a 1 + a 2 ) n + a 3 − a 1 + ( b 1 + c − a 1 − a 2 ) n − c + b 3 − b 1 − a 3 + a 1 d x } A n − 1 ( x ) + x a { ( a 2 − c ) x d − a 2 } A n − 1 ′ ( x )$
with $A 0 ( x ) = 1$, $a > 0$ and $d > 0$.
(ii)
Assume $b 1 ≥ a 1$ and $b 3 ≥ a 2 + a 3$. If $a 2 ≤ 0$, then ${ B n ( x ) } n ≥ 0$ is a generalized Sturm sequence.
Proof.
$( i )$ Because $b 2 = a 2 + c$, it is obvious that
$B n ( x ) = [ b 1 n + b 3 − b 1 + ( a 1 n + a 2 + a 3 − a 1 ) x ] B n − 1 ( x ) + ( c + a 2 x ) ( 1 + x ) B n − 1 ′ ( x ) ,$
It can be proven that $( i )$ holds by induction on n as follows.
As $n = 1$, we can obtain
$A 1 ( x ) = 1 a { a 2 + a 3 + b 3 − a 2 − a 3 d x } B 1 ( x ) = b 3 + ( a 2 + a 3 ) x .$
Thus, we have
$B 1 ( x ) = a ( 1 + x ) A 1 ( d 1 + x ) .$
By the induction hypothesis, it now turns out that
$B n − 1 ′ ( x ) = a n − 1 ( n − 1 ) ( x + 1 ) n − 2 A n − 1 ( d 1 + x ) − a n − 1 ( x + 1 ) n − 1 A n − 1 ′ ( d 1 + x ) d ( 1 + x ) 2 = ( n − 1 ) B n − 1 ( x ) 1 + x − d a n − 1 ( x + 1 ) n − 3 A n − 1 ′ ( d 1 + x ) .$
It follows from that recurrence relation (7) that, for $n ≥ 2$,
$a n ( 1 + x ) n A n ( d 1 + x ) = { ( ( a 1 + a 2 ) n + a 3 − a 1 ) ( 1 + x ) + ( b 1 + c − a 1 − a 2 ) n − c + b 3 − b 1 − a 3 + a 1 } B n − 1 ( x ) − ( c + a 2 x ) ( n − 1 ) B n − 1 ( x ) + ( c + a 2 x ) ( 1 + x ) B n − 1 ′ ( x ) = B n ( x )$
Thus, for $n ≥ 1$, we can prove that
$B n ( x ) = a n ( 1 + x ) n A n ( d 1 + x ) .$
$( i i )$ Evidently, in light of $( i )$, $B n ( x )$ forms a generalized Sturm sequence if and only if (iff) $A n ( x )$ forms a generalized Sturm sequence. The nonnegativity of the coefficients for $A n ( x )$ needs to be considered firstly. Let $A n ( x ) = ∑ k = 0 n A ( n , k ) x k$ for $n ≥ 0$. Then, according to the recurrence relation (7), we obtain
$A ( n , k ) = ( a 1 + a 2 ) n − a 2 k + a 3 − a 1 a A ( n − 1 , k ) + ( b 1 + c − a 1 − a 2 ) n − ( c − a 2 ) k + b 3 − b 1 + a 1 − a 2 − a 3 a d A ( n − 1 , k − 1 )$
for $n ≥ 1$. Following from the nonnegativity of ${ B ( n , k ) } n , k ≥ 0$, it holds
$a 1 + a 2 ≥ 0 , a 1 ≥ 0 , a 2 + a 3 ≥ 0$
Furthermore, by the hypothesis condition, we obtain
$b 1 + c − a 1 − a 2 ≥ c − a 2 ≥ 0 , ( b 1 + c − a 1 − a 2 ) − ( c − a 2 ) = b 1 − a 1 ≥ 0 , ( b 1 + c − a 1 − a 2 ) − ( c − a 2 ) + b 3 − b 1 + a 1 − a 2 − a 3 ≥ 0 .$
Thus, ${ B ( n , k ) } n , k ≥ 0$ is a nonnegative array. According to the recurrence relation (7) and Lemma 1, we can conclude that the polynomials $A n ( x )$ form a generalized Sturm sequence if $a 2 ≤ 0$. For the same reason, the polynomials $B n ( x )$ form a generalized Sturm sequence. □
For example, the row-generating function of the Bell triangle $a ( n , k )$ in Section 3 is $a n ( x ) = ∑ k = 0 n a ( n , k ) x k$. Then, the polynomials satisfy
$a n ( x ) = ( 1 + x ) a n − 1 ( x ) + ( 1 + x ) a n − 1 ′ ( x ) ,$
with $a 0 ( x ) = 1$. Using Theorem 2$( i )$, there exists an array $A ( n , k )$ such that
$a n ( x ) = ∑ k = 0 n a ( n , k ) x k = ( 1 + x ) n A n ( 1 1 + x )$
where $A n ( x )$ for $n ≥ 1$ satisfies the recurrence relation
$A n ( x ) = [ ( n − 1 ) x + 1 ] A n − 1 ( x ) − x 2 A n − 1 ′ ( x )$
where $A 0 ( x ) = 1$ and $A 1 ( x ) = 1$. Obviously, $A ( n , k ) = S ( n , n − k )$ for $n ≥ 1$. Applying Theorem 2 $( i i )$, it can be proven that ${ a n ( x ) }$ for $n ≥ 0$ is a generalized Sturm sequence.

Author Contributions

Methodology, R.R.Z. and J.Y.; validation, F.R.; writing, R.R.Z. All authors have read and agreed to the published version of the manuscript.

Funding

The first author was supported by the National Natural Science Foundation of China (NSFC No. 11501090) and the Natural Science Foundation of Hebei Province (A2019501024). The second author was supported by MOST 110-2115-M-017-002-MY2; The third author’s research was partially supported by the National Natural Science Foundation of China (NSFC No. 61807029).

Not applicable.

Not applicable.

Not applicable.

Conflicts of Interest

The authors declare no conflict of interest.

References

1. Chen, W.Y.C. Context-free grammars, differential operators and formal power series. Theor. Comput. Sci. 1993, 117, 113–129. [Google Scholar] [CrossRef] [Green Version]
2. Hao, R.X.J.; Wang, L.X.W.; Yang, H.R.L. Context-free Grammars for Triangular Arrays. Acta Math. Sin. Engl. Ser. 2015, 31, 445–455. [Google Scholar] [CrossRef]
3. Bóna, M.; Ehrenborg, R. A combinatorial proof of the log-concavity of the numbers of permutations with k runs. J. Combin. Theory Ser. A 2000, 90, 293–303. [Google Scholar] [CrossRef] [Green Version]
4. Ma, S.-M.; Wang, Y. q-Eulerian polynomials and polynomials with only real zeros. Electron. J. Combin. 2008, 15, 17. [Google Scholar] [CrossRef] [Green Version]
5. Ma, S.-M. An explicit formula for the number of permutations with a given number of alternating runs. J. Combin. Theory Ser. A 2012, 119, 1660–1664. [Google Scholar] [CrossRef] [Green Version]
6. Stanley, R.P. Longest alternating subsequences of permutations. Mich. Math. J. 2008, 57, 675–687. [Google Scholar] [CrossRef]
7. Zhu, B.-X.; Yeh, Y.-N.; Lu, Q. Context-free grammars, generating functions and combinatorial arrays. Eur. J. Comb. 2019, 78, 236–255. [Google Scholar] [CrossRef]
8. Ma, S.-M. Enumeration of permutations by number of alternating runs. Discret. Math. 2013, 313, 1816–1822. [Google Scholar] [CrossRef]
9. Aigner, M. A characterization of the Bell numbers. Discret. Math. 1999, 205, 207–210. [Google Scholar] [CrossRef] [Green Version]
10. Chen, X.; Liang, H.; Wang, Y. Total positivity of recursive matrices. Linear Algebra Its Appl. 2015, 471, 383–393. [Google Scholar] [CrossRef]
11. Sloane, N.J.A. The On-Line Encyclopedia of Integer Sequences. Available online: http://oeis.org (accessed on 30 January 2022).
12. Krall, H.L.; Frink, O. A new class of orthogonal polynomials. Trans. Amer. Math. Soc. 1945, 65, 100–115. [Google Scholar] [CrossRef]
13. Goldman, J.; Haglund, J. Generalized rook polynomials. J. Combin. Theory Ser. A 2000, 91, 509–530. [Google Scholar] [CrossRef] [Green Version]
14. Han, H.; Seo, S. Combinatorial proofs of inverse relations and log-concavity for Bessel numbers. Eur. J. Combin. 2008, 29, 1544–1554. [Google Scholar] [CrossRef] [Green Version]
15. Ma, S.-M. Some combinatorial arrays generated by context-free grammars. Eur. J. Comb. 2013, 34, 1081–1091. [Google Scholar] [CrossRef]
16. Barry, P. Exponential Riordan Arrays and Permutation Enumeration. J. Integer Seq. 2010, 13, Article 10.9.1. [Google Scholar]
17. Barbero, J.F. Salas, G.J. Bivariate generating functions for a class of linear recurrences: General structure. J. Comb. Theory Ser. A 2014, 125, 146–165. [Google Scholar] [CrossRef] [Green Version]
18. Théorêt, P. Hyperbinomiales: Doubles Suites Satisfaisant à Des équations aux Différences Partielles de Dimension et D’ordre deux de la Forme H(n,k) = p(n,k)H(n − 1,k) + q(n,k)H(n − 1,k − 1). Ph.D. Thesis, Université du Québec à Montréal, Montreal, QC, Canada, May 1994. [Google Scholar]
19. Théorêt, P. Fonctions génératrices pour une classe déquations aux différences partielles. Ann. Sci. Math. Québec 1995, 19, 91–105. [Google Scholar]
20. Liu, L.L.; Wang, Y. A unified approach to polynomial sequences with only real zeros. Adv. Appl. Math. 2007, 38, 542–560. [Google Scholar] [CrossRef] [Green Version]
Table 1. Some combinatorial sequences satisfying formula (3).
Table 1. Some combinatorial sequences satisfying formula (3).
$( a 1 , a 2 , a 3 , b 1 , b 2 , b 3 , c )$DescriptionEntry
(1,−1,1,0,1,1,0)Eulerian numbersA173018
(2,−1,1,0,1,1,0)Second-order Eulerian numbersA008517
(0,1,0,0,1,0,0)Surj$( n , k )$A019538
(1,1,0,0,1,0,0)Ward numbersA134991
(0,0,1,0,1,0,0)Stirling subset numbersA008277
(0,0,−1,−1,−1,0,0)Lah numbers $L n , k$A008297
(0,0,1,1,1,0,0)Unsigned Lah numbers $L ( n , k )$A105278
(−2,1,−2,0,0,1,0)Coefficients of Laguerre polynomials
in reverse order
A021010
(0,0,1,0,0,1,0)Binomial coefficientsA007318
(0,0,1,1,0,0,0)Stirling cycle numbersA132393
(0,0,1,−1,0,0,0)Stirling numbers of the 1st kind $s ( n , k )$A008275
(0,0,1,0,1,2,1)Production of the triangle of Stirling numbers
of the 2nd kind with
the Pascal’s triangle read by rows
A137597
(0,0,1,0,1,0,1)Set partitions without singletonsA217537
(0,0,1,0,2,1,2)Exponential Riordan Array
$[ exp ( sin h ( x ) ∗ exp ( x ) ) , sin h ( x ) ∗ exp ( x ) ]$
A154602
(0,1,0,0,2,1,1)$n ! n k$A196347
(0,1,0,0,2,2,1)Row-generating function is $n ! ∑ k = 0 n ( 1 + x ) n − k k !$A073474
(1,1,0,2,2,2,1)The number of $( n , k )$ labeled rooted Greg trees
$( n ≥ 1 , 0 ≤ k ≤ n − 1 )$
A048160
(2,−1,2,0,0,0,1)The number of fixed-point-free involutions
of $1 , 2 , … , 2 n$ having k cycles with entries of
opposite parities $( 0 ≤ k ≤ n )$
A161119
 Publisher’s Note: MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Share and Cite

MDPI and ACS Style

Zhou, R.R.; Yeh, J.; Ren, F. Context-Free Grammars for Several Triangular Arrays. Axioms 2022, 11, 297. https://doi.org/10.3390/axioms11060297

AMA Style

Zhou RR, Yeh J, Ren F. Context-Free Grammars for Several Triangular Arrays. Axioms. 2022; 11(6):297. https://doi.org/10.3390/axioms11060297

Chicago/Turabian Style

Zhou, Roberta Rui, Jean Yeh, and Fuquan Ren. 2022. "Context-Free Grammars for Several Triangular Arrays" Axioms 11, no. 6: 297. https://doi.org/10.3390/axioms11060297

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.